Smoking and finances: baseline characteristics of low income daily smokers in the FISCALS cohort - Kristy A. Martire; Philip Clare; Ryan J. Courtney; Billie Bonevski; Veronica Boland; Ron Borland; Christopher M. Doran; Michael Farrell; Wayne Hall; Jaimi M. Iredale; Mohammad Siahpush; Richard P. Mattick (BMC, 2017)
Abstract Background Financial stress is a barrier to successful smoking cessation and a key predictor of relapse. Little is known about the financial situation of low-income Australian daily smokers. This study aims to describe and investigate associations between the financial functioning, tobacco use and quitting behaviours of low income daily smokers. Methods Low-income Australian adult smokers in the 'Financial Intervention for Smoking Cessation Among Low-income Smokers (FISCALS) randomised clinical trial completed a structured telephone questionnaire. Results The median number of cigarettes typically smoked by the 1047 participants was 23 per day. The median spent on tobacco per week was AU$80. Three quarters (73.0%) reported some financial stress and 43.2% reported smoking-induced deprivation. Financial stress was significantly associated with deprivation (IRR: 1.23, 95% CI 1.21, 1.26, p < 0.001). There were no significant associations either between adjusted financial stress or deprivation and motivation to quit or certainty of quit success. Conclusions Financial stress and smoking induced deprivation were prevalent among low-income daily smokers, but they were not associated with motivation to quit. Smoking cessation interventions need to be responsive to the role financial stress plays in reducing quit attempts and increasing relapse. Trial registration Australian and New Zealand Clinical trials Registry ACTRN12612000725864 6/07/2012